Targeting B Cells and Plasma Cells in Autoimmune Diseases - Hofmann, Katharina; Clauder, Ann-Katrin; Manz, Rudolf Armin (Frontiers in Immunology, 2018)
Success with B cell depletion using rituximab has proven the concept that B lineage cells represent a valid target for the treatment of autoimmune diseases and has promoted the development of other B cell targeting agents. Current results confirmed that B cell depletion could be beneficial in various autoimmune disorders, but also showed that it could worsen the disease course in some patients. These finding may stress the fact that B lineage cells do not only produce pathogenic autoantibodies, but can also significantly contribute to control of inflammation. In this review, we will discuss the multiple pro-and anti-inflammatory roles B lineage cells play in autoimmune diseases in the context of recent findings using B lineage targeting therapies.